403 Saccular Aneurysms in the Post–Barrow Ruptured Aneurysm Trial Era. (1st April 2022) - Catapano, Joshua; Labib, Mohamed; Srinivasan, Visish M.; Nguyen, Candice; Rumalla, Kavelin; Rahmani, Redi; Cole, Tyler S.; Baranoski, Jacob F.; Rutledge, Caleb; Chapple, Kristina; Ducruet, Andrew F.; Albuquerque, Felipe; et al.
Abstract : INTRODUCTION: The Barrow Ruptured Aneurysm Trial (BRAT) was a single-center trial that compared endovascular coiling to microsurgical clipping in patients treated for aneurysmal subarachnoid hemorrhage (aSAH). However, because patients in the BRAT were treated more than 15 years ago, and because there have been advances since then—particularly in endovascular techniques—the relevance of the BRAT remains controversial. METHODS: All patients with a confirmed saccular aSAH treated at a single quaternary center from August 1, 2007, to July 31, 2019, were retrospectively reviewed. Patients were separated into two groups for analyses: microsurgery or endovascular intervention. The primary outcome analyzed for comparison was a poor neurological outcome, defined as a modified Rankin Scale (mRS) score >2. The secondary outcomes that were compared included retreatment rates for both therapies. RESULTS: Of the 1014 patients with aSAH during the study period, 798 (79%) were confirmed to have saccular aneurysms. Neurologic outcomes at =1-year follow-up did not differ between patients treated with microsurgery and those who received endovascular treatment (P=0.51). The number of retreatments was significantly higher among patients treated endovascularly (32/347, 9%) than among patients treated microsurgically (6/451, 1%) (P<0.001). The retreatment rate after endovascular treatment was lower in the PBRAT (9%) than in the BRAT (18%). CONCLUSION: Similar to results from the BRAT, results from the PBRAT era showed equivalent neurologic outcomes and increased rates of retreatment among patients undergoing endovascular embolization compared with microsurgery. However, the rate of retreatment after endovascular intervention was much lower in the PBRAT than in the BRAT.